2017
DOI: 10.5515/jkiees.2017.17.2.71
|View full text |Cite
|
Sign up to set email alerts
|

Tunable-Slot-Type Ground Radiation Antenna with Dual Band Operation Using LC Resonator

Abstract: A dual-band tunable-slot-type ground radiation antenna is proposed. The feeding structure consists of a coplanar waveguide and a lumped capacitor to excite currents for first-and second-order resonant modes of the ground. The resonant frequencies of both bands are controlled using a series combination of a capacitor and an inductor. The proposed design may be an attractive choice for mobile devices owing to its compact geometry and tunable operating frequencies. The measurement and simulation results of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Mode 1 resembles that of a half wave dipole that does not change phase across the ground plane. On the other hand, Mode 2 resembles that of a full wave dipole mode [42]. On the contrary to Mode 1, the current density of mode 2 is minimum at the middle of the longer edge of the ground plane.…”
Section: Coupling Mechanism and Modal Analysismentioning
confidence: 94%
“…Mode 1 resembles that of a half wave dipole that does not change phase across the ground plane. On the other hand, Mode 2 resembles that of a full wave dipole mode [42]. On the contrary to Mode 1, the current density of mode 2 is minimum at the middle of the longer edge of the ground plane.…”
Section: Coupling Mechanism and Modal Analysismentioning
confidence: 94%
“…Slot structures are commonly used to achieve bandwidth enhancement in multiband printed antennas. Traditional slot fractal shapes and other structures have been effectively used to design antennas with and multiband for a variety of wireless applications [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Sze et al [7] suggested a low profile dual-band Annular Ring Slot Antenna (ARSA) for the use in 2.4/5 GHz (WLANs).…”
Section: Introductionmentioning
confidence: 99%
“…However, the PIFA has more and more complicated antenna pattern to satisfy the various demands for wireless service such as 2G, 3G, and long‐term evolution (LTE). The mobile antennas evolve as a way to implement multiband using an impedance matching circuit in a simple antenna pattern including tunable antennas . From the 2010s, the mobile handsets utilize the metal rim or cover design to make mobile handsets aesthetic and strong mechanically.…”
Section: Introductionmentioning
confidence: 99%